Phenotypic and molecular states of IDH1 mutation-induced CD24-positive glioma stem-like cells - Haddock, Sara; Alban, Tyler J.; Turcan, S̨evin; Husic, Hana; Rosiek, Eric; Ma, Xiaoxiao; Wang, Yuxiang; Bale, Tejus; Desrichard, Alexis; Makarov, Vladimir; Monette, Sebastien; Wu, Wei; et al. (Neoplasia, 2022)
Mutations in IDH1 and IDH2 drive the development of gliomas. These genetic alterations promote tumor cell renewal, disrupt differentiation states, and induce stem-like properties. Understanding how this phenotypic reprogramming occurs remains an area of high interest in glioma research. Previously, we showed that IDH mutation results in the development of a CD24-positive cell population in gliomas. Here, we demonstrate that this CD24-positive population possesses striking stem-like properties at the molecular and phenotypic levels. We found that CD24 expression is associated with stem-like features in IDH-mutant tumors, a patient-derived gliomasphere model, and a neural stem cell model of IDH1-mutant glioma. In orthotopic models, CD24-positive cells display enhanced tumor initiating potency compared to CD24-negative cells. Furthermore, CD24 knockdown results in changes in cell viability, proliferation rate, and gene expression that closely resemble a CD24-negative phenotype. Our data demonstrate that induction of a CD24-positive population is one mechanism by which IDH-mutant tumors acquire stem-like properties. These findings have significant implications for our understanding of the molecular underpinnings of IDH-mutant gliomas.
Available online 7 April 2022
Gesehen am 24.06.2022